Pengaruh Penggunaan Kemas Ulang Informasi Melalui TikTok terhadap Literasi Informasi Mahasiswa Manajemen Universitas Jambi - Suci Riqsyah Amaliah; Ratih Anjelia Guspamora; Ari Pratama (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
The development of social media has brought about rapid changes in the way information is accessed and consumed. One form of information adaptation is information repackaging that directs and re-presents information in a more interesting and easy-to-understand format. This study aims to determine the extent of the influence of the use of information repackaging through TikTok on the information literacy of Management Students at Jambi University. The study used a quantitative approach with data collection techniques through questionnaires. The results of the study showed that there was an influence of the use of information repackaging through TikTok of 63.0% while the rest (100% -63.0%) was 37% influencing other variables outside this study. The customized R square value of 63% is included in the moderate category, which shows the influence of information repackaging through TikTok on students' information literacy depending on how users use the application.